Synthesis, Characterization, and Applications of Copper Nanoparticles. (2nd January 2017) - Din, Muhammad Imran; Rehan, Rida
ABSTRACT: Copper nanoparticles with different structural properties and effective biological effects may be fabricated using new green protocols. The control over particle size and in turn size-dependent properties of copper nanoparticles is expected to provide additional applications. Various methods for the synthesis of copper nanoparticles have been reported including chemical methods, physical methods, biological methods, and green synthesis. Biological methods involve the use of plant extracts, bacteria, and fungi. Commendable work has been done regarding the synthesis and stability of copper nanoparticles. There is a need to summarize the behavior of copper nanoparticles in different media under various conditions. Here, a complete list of the literature on the synthesis of copper nanoparticles, their properties, stabilizing agents, factors affecting the morphology, and their applications is presented. The importance of copper nanoparticles compared to other metal nanoparticles are due to high conductivity. Methods for the synthesis of copper nanoparticles, including green protocols using plants and micro-organisms compared chemical methods, have also been reviewed.